Application of Consumer Behavior Analysis in Marketing Strategies - Liu, Xiaowei (Transactions on Economics, Business and Management Research, 2024)
With the rapid development of digitalization, consumer behavior is becoming increasingly complex, with choices becoming more diverse and demands more personalized and intricate. This presents both new opportunities and challenges for businesses' marketing strategies. In such an environment, the importance of consumer behavior analysis is gradually highlighted. In-depth research into various stages of consumer decision-making enables insight into consumers' psychology, needs, and preferences. From the initial awareness stage to information gathering, evaluation, selection, purchase decision, and post-purchase behavior, each stage presents rich market opportunities. Simultaneously, in terms of product strategy, based on consumer behavior analysis, companies can develop products that better meet market demands, catering to personalized consumer needs. In pricing strategy, more competitive prices can be formulated based on consumers' ability to pay and price sensitivity. In promotion strategy, suitable promotional methods and channels can be chosen based on consumers' information acquisition channels and preferences. In distribution strategy, distribution networks and channel layouts can be optimized based on consumers' purchasing habits and convenience. Through in-depth analysis of consumer behavior, companies can more accurately meet market demands and achieve competitive advantages.